Determining the Determiners - Cook, David (Centre for Language in Education and Development, 2014)
David cook in his paper seeks to unravel the mystery behind the deep-seated problems for second language speakers of English in finally grasping the subtleties in usage of the basic English determiners - 'the', 'a'/'an' and 'zero'. His reasons for these problems are attributed to certain linguistic and non-linguistic sources, but certainly not to their level of intelligence. Having identified the problems, Cook tries to find a way of remedying them. his suggestions of solutions pertain to both linguistic and applied linguistic areas based on certain requirements; an adequate pedagogical grammar of English determiners for ESL learners, an appropriate textbook, a well-trained teacher, an appropriate learning environment, a superabundant supply of rich examples of data in different apt contexts, and an appropriate methodology.